Real-world natural passivation phenomena can limit microplastic generation in water - Xiao, Liwen; Gounko, Iouri; Shvets, Igor; Moebius, Matthias; Li, Dunzhu; Boland, John (My University, 2022)
Previous studies using Deionized (DI) water found that household plastic products used in food preparation and storage are a local and immediate source of extremely high quantities of microplastics (MPs) released directly into to the human body and the environment. However, DI water is rarely used outside of laboratories. Here, MP release from plastic products exposed to ordinary drinking water was studied. To facilitate this study, the concept of Synthetic drinking water (SDW) was introduced, which involved preparing water in accordance with the WHO standard but modified to mimic the composition of local Tap drinking water (TDW). It was found that the level of MP released from plastics exposed to TDW and SDW are very similar, demonstrating that SDW is an appropriate real-world reference standard to test MP release levels from plastic products. In contrast with the use of DI water, plastics exposed to hot (40–100 ◦C) SDW and TDW showed the progressive development of a Copper (II) oxide (CuO) passivation film due to the presence of Cu2+ ions in the water samples. Similar passivation films formed on 97% of all food grade plastics. Longitudinal studies of polypropylene products (kettles) exposed to boiling TDW during normal use resulted in the continuous growth of CuO passivation films that ultimately yielded a 99.8% reduction in MP release. Engineered reductions in MP release levels were observed following separate controlled exposures to SDW with elevated Cu2+ levels, yielding denser CuO passivation films. This study underscores the importance of reproducing real world conditions in microplastic studies and also the potential for nature-inspired engineered films to mitigate against the release of MPs and the possibility of sustainable MP-free products.
PUBLISHED
Keywords: Deionized (DI) water; Microplastics (MPs) release; Kettles; CuO passivation films; Synthetic drinking water (SDW); Natural passivation phenomena; Creative Technologies; Smart & Sustainable Planet; microplastics; Environment and housing; Health